Green roofs as a solution to inundations problem in urban environments (Gaceta Técnica, 2018)
This research was carried out using mathematical models in order to compare the runoff from an urban planning with handmade tiles roofs in actual conditions, with one where structures or storage devices and water retention in houses, yards are used, parcels, streets and housing complexes in general. A study area in the state of Lara, Venezuela, in Palavecino municipality, near Quebrada Tabure, was selected and green roofs are considered from the point of view of reducing runoff. An application called "TechosVerdes.py" was made under the license free Python program with approximately 4600 code lines was developed to calculate hydrographs from roofs, patios, streets and green areas, based on a mosaic created with type raster images in the Quantum Gis program. The research was based on the direct comparison of thirteen scenarios where green roofs were used and additionally, storage tanks and parapets, with an original scenario on current conditions without alterations. In the hydrographs produced by hypothetical scenarios it was determined that the peak flow decreases squashing the hydrograph